2017
DOI: 10.1200/jco.2017.35.8_suppl.37
|View full text |Cite
|
Sign up to set email alerts
|

Significant and sustained reduction in chemotherapy errors though improvement science.

Abstract: 37 Background: The majority of children with cancer are now cured with highly complex chemotherapy regimens incorporating multiple drugs and demanding monitoring schedules. The risk for error is high and can occur at any stage in the process, from order generation through pharmacy formulation to bedside drug administration. Our objective is to describe a program to eliminate errors in chemotherapy use among children. Methods: To increase reporting of chemotherapy errors, we supplemented the hospital-reporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It utilizes an interprofessional team approach with the integration of evidence-based practices, which are continuously re-evaluated with the goal of continuously improving care Institute of Medicine. 6 The team huddle is one such tool; and in fact has been identified as a successful means of facilitating team communication, in addition to addressing root cause analyses of chemotherapy associated sentinel events Blough & Walrath 7 Morrissey et al, 8 Bunnell et al, 5 Weiss et al 1 For example, Bunnell et al, 5 as part of a process improvement initiative identified four major issues arising from lack of a team approach to oncology chemotherapy patients. These included:…”
Section: The Team Huddlementioning
confidence: 99%
See 1 more Smart Citation
“…It utilizes an interprofessional team approach with the integration of evidence-based practices, which are continuously re-evaluated with the goal of continuously improving care Institute of Medicine. 6 The team huddle is one such tool; and in fact has been identified as a successful means of facilitating team communication, in addition to addressing root cause analyses of chemotherapy associated sentinel events Blough & Walrath 7 Morrissey et al, 8 Bunnell et al, 5 Weiss et al 1 For example, Bunnell et al, 5 as part of a process improvement initiative identified four major issues arising from lack of a team approach to oncology chemotherapy patients. These included:…”
Section: The Team Huddlementioning
confidence: 99%
“…Research pertaining to the role and process of Oncology Nurse Practitioner (ONP) patient navigation in the chemotherapy suite is limited, yet it is maintained that management of patients receiving chemotherapy requires a team effort Weiss et al, 1 and that the navigation process requires the use of navigation tools Johnson 2 A recent ethnographic study in the United Kingdom (UK), looked at the scope of clinical practice of nurse-lead clinics which included both chemotherapy nurses, and advanced practice nurses (APN's). It was found that different levels of care existed amongst the clinics, and that these levels of care were driven by the level of nursing autonomy and scope of practice, which was heavily influenced by medical consultants Farrell et al 3 Studies have confirmed the importance of good ONP or PA, oncologist, oncology nurses, and pharmacist.…”
Section: Mini Reviewmentioning
confidence: 99%